Analisis Klasifikasi Kemampuan Kalkulus Mahasiswa Berdasarkan Gender Berdasarkan Skor Asesmen - Lalu Sucipto; Habibi Ratu Perwira Negara (Ulul Albab: Majalah Universitas Muhammadiyah Mataram, 2026)
This study aims to analyze and classify students’ calculus abilities and to examine differences in these abilities based on gender. The study employed a quantitative approach with a descriptive–comparative research design. The research subjects consisted of 104 students from four classes. The research instrument was a calculus essay test consisting of three items. Data analysis techniques included descriptive statistical analysis, classification of calculus ability into five categories, and testing for gender-based differences using an independent samples t-test, supported by the Mann–Whitney test. The results showed that students’ calculus abilities were predominantly in the low (39.42%) and moderate (35.58%) categories, while the high and very high categories accounted for only 13.46% and 11.54%, respectively, and no students were classified in the very low category. The findings indicate that students’ calculus abilities still need to be improved and are not significantly influenced by gender.